Pengaruh Kesejahteraan Hidup Terhadap Kesehatan Mahasiswa Rantau Universitas PGRI Wiranegara - Rima Melati; Sugeng Pradikto (Student Research Journal, 2025)
This study aims to analyze the influence of well-being on the health of regional students at PGRI Wiranegara University. Using a quantitative approach with an explanatory survey design, data was collected through a structured questionnaire that included indicators of well-being (economic conditions, quality of housing, social support, mental health, and access to health services) as well as regional student health (physical, mental, and healthy lifestyles). Data analysis includes classical assumption tests, and simple linear regression to measure the relationship between independent and dependent variables. The validity and reliability of the instrument were tested through Pearson and Cronbach's Alpha correlations. The results of the study are expected to provide comprehensive insights into how well-being affects the health of regional students. These findings are expected to be the basis for universities in formulating strategic policies to improve the welfare and health of students, thereby supporting their academic success holistically.